2019
DOI: 10.3892/etm.2019.7613
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic properties of dexmedetomidine provide neuroprotection in rats following cerebral ischemia‑reperfusion injury

Abstract: Dexmedetomidine (Dex) is a sedative and analgesic agent that is widely administered to patients admitted to the intensive care unit, and has been demonstrated to result in hypothermia. Many patients have been revealed to benefit from therapeutic hypothermia, which can mitigate cerebral ischemia/reperfusion (I/R) injury following successful cardiopulmonary resuscitation. However, studies investigating the efficacy of Dex in I/R treatment is lacking. The present study aimed to investigate the efficacy of Dex in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…Those results demonstrate that overactivation of autophagy may lead to apoptosis and ferroptosis, whereas inhibition of autophagy may attenuate apoptosis and improve neurological function. Previous studies [54] and the results of this study have demonstrated that overactivation of autophagy could provoke apoptosis and ferroptosis, and inhibition of autophagy could alleviate PCABI.…”
Section: Discussionsupporting
confidence: 59%
“…Those results demonstrate that overactivation of autophagy may lead to apoptosis and ferroptosis, whereas inhibition of autophagy may attenuate apoptosis and improve neurological function. Previous studies [54] and the results of this study have demonstrated that overactivation of autophagy could provoke apoptosis and ferroptosis, and inhibition of autophagy could alleviate PCABI.…”
Section: Discussionsupporting
confidence: 59%
“…Dexmedetomidine associated with hypothermia reduces brain damage, improves neurological outcome, and increases the survival rate of the hippocampal CA1 neurons, compared to saline [ 46 ]. The increase in expression of ZO-1 in mild hypothermia + dexmedetomidine compared to normothermia + dexmedetomidine may be attributed to hypothermia alleviating neurocyte apoptosis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothermia was corrected by the placement of an overhead radiant warmer and a decrease of the dexmedetomidine infusion to 0.2 µg/kg/h. Additional evidence for the potential impact of α 2 -adrenergic agonists on thermoregulation and their potential role in the development of hypothermia is provided by animal data [20][21][22].…”
Section: Discussionmentioning
confidence: 99%